2012
DOI: 10.1074/jbc.m112.369561
|View full text |Cite
|
Sign up to set email alerts
|

Lipodepsipeptide Empedopeptin Inhibits Cell Wall Biosynthesis through Ca2+-dependent Complex Formation with Peptidoglycan Precursors

Abstract: Background:The mechanism of action of the potent antibiotic empedopeptin was not known. Results: Empedopeptin forms calcium-dependent complexes with peptidoglycan precursors, particularly lipid II. Conclusion: Bacterial cell wall synthesis is blocked by sequestration of the bactoprenol carrier. Significance: This mechanism is proposed for a wider class of structurally related antibiotics including empedopeptin, tripropeptins, and plusbacins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…In Vitro Synthesis of Lipid II-Lipid II was synthesized as described with minor modifications (21). In brief 100 nmol of UDP-GlcNAc in 50 mM Bistris propane, pH 8.…”
Section: Methodsmentioning
confidence: 99%
“…In Vitro Synthesis of Lipid II-Lipid II was synthesized as described with minor modifications (21). In brief 100 nmol of UDP-GlcNAc in 50 mM Bistris propane, pH 8.…”
Section: Methodsmentioning
confidence: 99%
“…In depth analysis on the mechanism of action revealed that empedopeptin interferes with peptidoglycan biosynthesis by sequestering the cell wall building block lipid II as its primary target in a calcium-dependent fashion (Müller et al, 2012). Calcium ions increase the antibacterial activity of empedopeptin by strengthening the interaction of the net-negative antibiotic with its target and with phospholipids in the cytoplasmic membrane.…”
Section: Empedopeptin Tripropeptins and Plusbacinsmentioning
confidence: 99%
“…Although it contains a 14‐carbon myristic tail, empedopeptin has a net negative charge and remains water soluble. Empedopeptin may have eventual clinical considerations, as preclinical studies suggest significant in vitro and in vivo activity against antibiotic‐resistant pathogens, low overall toxicity, and a favorable pharmacologic profile 19 . Using membrane preparations and lipid II precursor components, empedopeptin was shown to bind to lipid II with a 2:1 stoichiometry.…”
Section: Basic Structure and Function Of Microbial Cell Wallsmentioning
confidence: 99%
“…Notably, Ca 2+ ions are essential for the interaction between this net negatively charged peptide and lipid II. Empedopeptin does not appear to cause membrane depolarization 19 . Given their structural similarities, it is possible that the tripropeptins and plusbacins may also target lipid II in a similar fashion 19 .…”
Section: Basic Structure and Function Of Microbial Cell Wallsmentioning
confidence: 99%